Therapeutic abdominoplasty: Report of a case. (2015) - Petrakis, Ioannis; Xenaki, Sofia; Andreou, Alexandros; Panagiotakis, Georgιοσ; Chalkiadakis, George
Highlights: Excessive drooping belly may lead to severe issues majorly affecting the person's health as well as the quality of life. Abdominoplasty could be used not only for cosmetic purposes but also for therapeutic purposes by eliminating morbidity and improving the quality of life. Abstract: Background: Abdominoplasty is a surgical procedure which is commonly used for cosmetic purposes. However, there are very few reports in the world literature describing the abdominoplasty procedure for therapeutic purposes rather than for cosmetic reasons. Methods: A 58 year old female presented with an excessive drooping belly and a concomitant minor umbilical stoma hernia, who suffered from chronic back pain, urinary incontinence, nerve atrophy of the low extremes, central-type obesity, gastric disorders, and spinal osteophytes who underwent abdominoplasty and umbilical hernia repair. Result: On discharge from the hospital after 11 days, the patient mentioned satisfactory elimination of the back pain as well as amelioration of the urinary incontinence. Within 14 months after the operation, the patient noticed extreme improvement of ambulation and postural stability as well as complete disappearance of the neuro-myodystrophy. Conclusion: Wide abdominal rectus plication abdominoplasty should be considered to be performed for therapeutic purposes when major health problems occur.